Nucleotide effects on kinetic properties of mitochondrial ATPase (Revista Española de Fisiología, 1987)
The hydrolytic activity of mitochondrial ATPase, both in its soluble form as F1-ATPase, or as membrane bound in whole mitochondria, was affected by the presence of free nucleoside di- or triphosphates; these effects were largely depending not only on their concentration but also on the substrate concentration.The existence of a regulatory site or sites is proposed; these sites would have a higher affinity for the free nucleoside triphosphates than for the diphosphates, and the interaction of any of these nucleotides with the proposed regulatory site or sites would lead to an activation.The nucleotide regulatory site or sites seem to be different from the anion binding sites since neither free ATP nor free GTP compete with activating or inhibitory anions.